PENILAIAN DERAJAT ASMA DENGAN MENGGUNAKAN ASTHMA CONTROL TEST (ACT) PADA PASIEN ASMA YANG MENGIKUTI SENAM ASMA DI PEKANBARU - Desta Reviona (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTAsthma is a chronic inflammatory disorder of the airways in which many cell and cellular elements play a role. Asthma gymnastic is one of the recommended exercise therapy to help the process of rehabilitation in patients with asthma. To assist in the management of asthma besides of rehabilitation by following the asthma exercise, it is necessary to control the asthma. Asthma Control Test (ACT) is a screening test in the form of a questionnaire on clinical judgement to know asthma is controlled or not. The research design useing descriptive study with cross sectional approachment. The sampling technique used total sampling with 31 samples obtained. Result showed that asthma patients who followed gymnastics asma were in the age group 21-30 years old (41,94%), most commonly happened in female (70,97%), most common had comorbidities (58,06%), most common patients had a family history of asthma (74,20%), the length of time following the most gymnastics was asthma gymnastics < 3 month of people (61,30%). The degree was the most severe asthma persistent (54,84%), assessment of asthma control was the most uncontrolled asthma (45,16%)Key word : Asthma, Asthma gymnastics, Asthma Control Test (